Peningkatan Pengetahuan Warga RT 05 RW 01 Pondok Labu Terhadap Alur Pelayanan Penyakit Hipertensi di Fasilitas Kesehatan dan Rumah Sakit - Muthia, Ayu; Efanti, Eni; Tyas, Delina Ayuning (Jurnal Abdimas Jatibara, 2024)
Hypertension, often referred to as the "silent killer," manifests without noticeable symptoms and can lead to serious health complications. It occurs when blood pressure exceeds 130 mmHg systolic and 80 mmHg diastolic. A precursor to conditions such as stroke, heart disease, and kidney failure, hypertension is the leading cause of death worldwide, affecting more than one billion people annually. Prevalence increases with age, potentially reaching 60% in populations over the age of 60. Without preventive measures, the number of hypertension cases worldwide is projected to increase by 20% to 1.5 billion by 2025. This study aims to improve community understanding of the hypertension treatment process within both healthcare facilities and hospitals. Methods This community initiative targeted residents of RT 05 RW 01 in Pondok Labu, Cilandak, South Jakarta. The intervention included educational sessions on hypertension, covering its definition, recommended actions when experiencing it, and elucidating the facilities and procedures involved in seeking healthcare in both primary care and hospital settings. The program consisted of three phases: preparation, implementation, and evaluation. The Results of 15 targeted residents, 11 actively participated in the assessments and educational sessions. The majority were women aged 36 to 55 years. Blood pressure assessments revealed that 54.55% had elevated levels. In addition, 63.64% were classified as overweight based on BMI measurements. The initiative successfully increased community knowledge regarding hypertension and the healthcare processes involved. The study highlights the importance of health education in improving public awareness and emphasizes the need for a holistic approach in managing risk factors such as excess weight. Effective coordination between hospital administration and medical teams is crucial in providing clear information and ensuring timely healthcare services for hypertensive patients.